General Principles of Modern Immunosuppressive Therapy - O. S. Nykonenko (Transplantation and artificial organs, 2021)
Immunosuppressive therapy is the most important component of drug treatment after organ transplantation. The goal of immunosuppression is to prevent acute and chronic rejection while maximizing patient survival, and long-term graft survival remains a major therapeutic challenge before and after organ transplantation. However, the benefits of immunosuppressive therapy must be balanced against the side effects and underlying toxicity of the drugs used.Immunosuppressants can be classified as induction agents, maintenance therapy, treatment of acute rejection and chronic rejection, and antibody directed therapy. Although induction therapy remains a subject of debate in the field of organ transplantation, it is still used in most transplant centers. Protocols for maintenance immunosuppressive therapy are more or less standardized and include, as a rule, three drugs, a calcineurin inhibitor, an antimetabolite, and a glucocorticoid. The presence of HLA antibodies in transplantation candidates and the development of de novo antibodies after transplantation remain a serious therapeutic problem before and after organ transplantation. In this lecture, we will look at the drugs used to induce and maintain immunosuppression, as well as their effectiveness in preventing side effects.